A Review of Zubair Hasan’s Book (2021) “Some Controversial Topics in Islamic Economics – A Reconciliatory Approach”, Islamic Economics Institute, KAU Press. - Abubakar Lamido, Abdullahi (Journal of King Abdulaziz University: Islamic Economics, 2023)
Two issues deserve special attention in the development of Islamic economics and finance. The first is the need to develop a consensus around some fundamental topics that, unfortunately, have gradually lost attention in the current literature of the discipline, a task that requires the attention of both current and emerging generations of Islamic economists. The second is imperative to collect, summarize and articulate these consensus positions in textbooks and readings that can serve as authoritative and ready-for-use references for teaching and research. The book under review is a welcome response to both of these concerns. In ten brief chapters, the author identifies and elucidates some relevant but mostly controversial topics to reconcile scholars’ divergent positions. These topics include but are not limited to labour, wealth, and welfare; higher education and human development in Muslim countries; sustainability, growth, and the environment; the relationship between profits and factors of production; and mortgage lending and housing finance. Whether the book has succeeded in reconciling the controversy is itself controversial; some readers may consider that the author has only succeeded in summarizing and reiterating his long-held positions on certain topics, including scarcity, his critique of risk-sharing and the dictum "no risk, no gain" in Islamic finance, and his questioning of the "mathematization" and "econometricization " of Islamic economics. Despite this, this book is a valuable and informative addition that could spark a new wave of research and discussion on crucial topics that have yet to receive less attention in recent studies on Islamic economics and finance.